(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prasetya DN, Hamim, Sulistyaningsih YC. 2022. Physiological and ultrastructural studies of Jatropha curcas and Reutealis trisperma in response to gold-mine tailings. Biodiversitas 23: 3471-3479. Heavy metal contamination through tailings from mining pollutes the environment and harms human health. This study aimed to analyze physiological, especially ultrastructural changes and the photosynthetic activities of Jatropha curcas and Reutealis trisperma in response to gold mine tailings. J. curcas and R. trisperma were grown in 8 kg of polybags and treated with 0%, 50%, and 100% gold mine tailings for three months before examining their morphological, physiological, and leaf ultrastructure. The results showed that gold mine tailings with 50% and 100% concentrations affected the growth of both species. This was indicated by reduced plant height, total leaf number, shoot, root dry weight, and decreased chlorophyll and carotenoid content. Furthermore, treatment of gold mine tailing at 50% and 100% induced lipid peroxidation, indicated by the significant increase in leaf malondialdehyde content. The photosynthetic and transpiration rates at 90 days after treatment decreased with the increase in gold mine tailings concentration. The leaf ultrastructure analysis showed high-level tailings of treatment-induced ultrastructure alteration of J. curcasand R. trisperma. However, these changes did not significantly affect the photosynthesis rate, hence the plants survived until the end of the observation period. The overall effect of tailings on R. trisperma was lower than on J. curcas, suggesting that R. trisperma had higher adaptability than J. curcas.